Platon Kostecki jako poeta jubileuszowy – jubileusze Platona Kosteckiego - Budrewicz, Tadeusz (Colloquia Litteraria, 2023)
The article discusses occasional poems by Plato Kostecki (1832–1908) – a poet and journalist, a long-time editor of “Nowa Reforma”, an ethnic Ruthenian and Polish patriot. His political goal was the independence of Poland united by the union with Ukraine. He repeatedly formulated this goal during toasts and poems written to commemorate the jubilees of famous public figures and in many speeche at celebrations in Lviv. Kostecki’s occasional poems integrated the inhabitants of Galicia during the period of national captivity. The popular poet lived to see several anniversaries of his journalistic work. The most important one took place in 1888. The course and echoes of this ceremony allow for a thesis that it was a political pretext to remind Poles of the 25th anniversary of the anti-Russian uprising in 1863.